Libertad religiosa del menor y relaciones paterno-filiares: conflictos - Asensio Sánchez, Miguel Ángel (2015)
Religious conflicts within the family are dealt with differently by the law depending on if they take place between the parents, normally in situations of matrimonial crisis, or between the parents and the children subject to parental authority. Conflicts between parents and children deal with two basic principles: that of the minor's authonomy when exercising his/ her right which is a consequence of the minor being a full subject of Law, and the legal-constitutional principle of the interest of the minor. In cases where the minor has natural legal capacity, then there is no real collision between the children's and the parents' religious freedom right to choose the child's religious education, as recognized under art. 2.1c) of LOLR (Religious freedom law) but there is instead an abuse in exercising parental authority. On the other hand, when the minor the child does not have such natural legal capacity, we are dealing with a problem of limits of parents when exercising the right contained in art. 2.1c) of LOLR which responds to a scheme of right/freedom and not to one of right/ function. For this reason, this right is aimed at satisfying the parents' interest and not those of the minor; this right will be relevant since it is part of public oder as regards minors, and public order is one of the limits of religious freedom according to art. 3.1 of LOLR
Keywords: Katholische Kirche; Katholische Kirche; Katholische Kirche; Katholische Kirche; Religionsfreiheit; Minderjährigkeit; Eltern; Kind; Religiöse Erziehung; Familie; Familie; Kind; Kind; Erziehung; Kindeswohl; Konfliktlösung; Menschenrecht; Minderjähriger; Rechtsfähigkeit; Religionsfreiheit